2020
DOI: 10.1039/c9na00730j
|View full text |Cite
|
Sign up to set email alerts
|

ZnAl2O4 decorated Al-doped ZnO tetrapodal 3D networks: microstructure, Raman and detailed temperature dependent photoluminescence analysis

Abstract: 3D network of ZnO:Al tetrapods decorated with ZnAl2O4 particles were synthesised by FTS. Al-doping was confirmed by the broadening and shift of the peak position of the 14 K NBE emission and by the bandgap shift to higher energy due to a Burstein–Moss effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…46 The broad band peaking at 1106 cm −1 is attributed to the 2LO mode. 47,48 It is also noticed that there is a variation in the peak position, which could be attributed to the substitution of Cu 2+ ions for the Zn 2+ ions in the ZnO host lattice.…”
Section: Resultsmentioning
confidence: 98%
“…46 The broad band peaking at 1106 cm −1 is attributed to the 2LO mode. 47,48 It is also noticed that there is a variation in the peak position, which could be attributed to the substitution of Cu 2+ ions for the Zn 2+ ions in the ZnO host lattice.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, they also reported a thorough PL analysis of the synthesized materials. 24 Shabani, et al reported the applicability of Al-doped ZnO in low-loss plasmonic metamaterials by employing a combination of Optical and Density Functional Theory calculations; the finding of this particular work showed a pronounced excited mode as well as an enhanced metallic property at higher level of Al doping. 25 The effect of Au on ZnO structure was also investigated considering Al-doped ZnO seed layer through ultrasonic spray pyrolysis approach for CO 2 sensing applications.…”
mentioning
confidence: 86%
“…Tetrapod nanostructures show very promising technological potential in view of their applications in variety of elds. [122][123][124][125] 3D CdS tetrapod nanostructures possess unique morphology with excellent optical and electronic properties for various applications and particularly photocatalytic applications due to their superior light-harvesting ability. 126,127 These nanostructures have gained great attention in the recent past due to their unique structure extended in the surrounding which facilitates their assembly and networking for obtaining/tailoring desired mechanical strength and physiochemical properties.…”
Section: Basic Properties Of Cdsmentioning
confidence: 99%